A loosely coupled architecture for automatic composition of web services applications. (7th July 2014) - Zuñiga, Juan Carlos; Pérez–Alcázar, José J.; Digiampietri, Luciano A.; Barbin, Silvio Ernesto
Semantic web research aims to provide mechanisms to combine several web services to offer a new value–added service that satisfies the user's request. A number of methods and tools have been proposed for this purpose. However, none of these approaches offers a complete solution from the standpoint of a decoupled, inter–organisational, domain–independent and ready for use by end users who do not have an in–depth technical knowledge. To overcome these limitations, this paper provides a loosely coupled architecture to develop applications based on web services composition, in which architectural modules can be integrated in different ways, ranging from inter–organisational sources, which support different levels of automation and composition methods, to diverse application domains. We described the input and output requirements for each module and implemented the following decoupled modules: interface (for non–technical users), translator (using the ANTLR tool), composer (using a hierarchical planner) and executor (based on workflows).